The Data Observatory, a vehicle to foster digital economy using natural advantages in astronomy in Chile. Issue Volume 14:Issue A30(2018) (August 2018) - Arancibia, Demián; Bayo, Amelia; Cabrera-Vives, Guillermo; Föster, Francisco; González, Roberto; Hamuy, Mario; Carlos Maureira, Juan; Quinn, Peter; Rada, Juan; Rodriguez, Gabriel; Santander-Vela, Juande; Tarenghi, Massimo; et al.
Abstract: The Astroinformatics Program is funded by the Chilean Economy Ministry's (FIE Grant FIE-2016-V022, CORFO Grant 16IFI6626) with the mission to identify and initiate investments to foster Chilean Digital Economy, using Astronomy data-centric tools (known as astroinformatics). Over 2017 we worked with communities across sectors identifying opportunities to achieve the program mission, the Data Observatory vision emerged from that work and will guide design activities throughout 2018.